The Role of H2O in Subduction Zone Magmatism - Grove, Timothy L.; Till, Christy B.; Krawczynski, Michael J. (Annual Review of Earth and Planetary Sciences, 2012)
Water is a key ingredient in the generation of magmas in subduction zones. This review focuses on the role of water in the generation of magmas in the mantle wedge, the factors that allow melting to occur, and the plate tectonic variables controlling the location of arc volcanoes worldwide. Water also influences chemical differentiation that occurs when magmas cool and crystallize in Earth's continental crust. The source of H2O for arc magma generation is hydrous minerals that are carried into Earth by the subducting slab. These minerals dehydrate, releasing their bound H2O into overlying hotter, shallower mantle where melting begins and continues as buoyant hydrous magmas ascend and encounter increasingly hotter surroundings. This process is controlled by plate tectonic variables that ultimately influence the location of the active volcanic arc above subduction zones. Water also modifies the thermodynamic properties of melts, leading to the unique chemical composition of arc volcanic rocks and Earth's continental crust.
Keywords: arc magmas